Shifting challenges for coastal green cities - Thanh, Nguyen Van; Le, Dang Thanh; Thinh, Nguyen An; Lan, Tran Dinh; Hens*, Luc (Vietnam Journal of Earth Sciences, 2017)
“Green cities” offer a systematic approach to a significant part of the nowadays urban complexity. The concept dovetails in the “healthy city” idea launched by the World Health Organization, but is equally associated with “sustainable” and “smart cities”. During the past decades planning for “green cities” shifted, incorporating new ideas as sustainable development and IT-driven management instruments for smart cities. Contemporary cities continue to face major environmental challenges. Replying to this dynamic context is a main task for cities during the coming decades of the millennium. As most of the (major) cities worldwide are located at the edge of the continents, supporting water-bound activities, they show a significant “blue economy” aspect. This paper reviews the historical context of the science aspects of “green cities” and the related approaches. Four main challenges for livable (coastal) cities today are discussed, taking into account the continuous changes and the almost permanent transition cities face. Climate change effects as sea level rise and extreme weather conditions, affect directly coastal cities; providing enough drinking water is a long standing and increasing problem; ports face particular and specific environmental problems which are in need of a tailored management; and sufficient accessible green areas remain of primary concern for any green city. Cross cutting through these issues are among others mobility and sustainable urban design.These major challenges will necessitate new processes of decision making. Long term planning is essential. This includes among others green infrastructure, systematic investment in natural areas (both on land and in the marine environment), cleaner technology innovations (on water treatment, low carbon emission technology, advanced waste prevention and treatment management, green roofs, and (artificial) wetlands), and the use of smart, IT-driven solutions.References Akcin M., Kaygusuz A., Karabiber A., Alagoz S., Alagoz B.B., Keles C., 2016. Opportunities for energy efficiency in smart cities. Smart grid congress and fair (ICSG), Istanbul, Turkey. IEEE Xplore document DOI:10.1109/SGCF.2016.7492425. Avin U., Holden D., 2000. Does your growth smart? Planning 66(1), 26-29. Bosh O., Nguyen Nam, Nguyen Van Thanh, 2016. Systems thinking for everyone. The journey from theory to making an impact in Vietnam, pp.126. Syspac PTY Ltd., Australia. Boulos, J., 2016. Sustainable Development of Coastal Cities-Proposal of a Modelling Framework to Achieve Sustainable City-Port Connectivity. Procedia - Social and Behavioral Sciences, 216(6), 974-985. Camarsa G., Toland J., O’Hara E., Hudson T., Jones W., Thorpe E., Théirgnot C., 2010. LIFE and local authorities. Helping regions and municipalities tackle environmental challenges. pp.56. Publications Office of the European Union, Luxemburg. Castro M. de Fatima, Mateus R., Braganca L., 2015. A critical analysis of buildings sustainability assessment methods for healthcare buildings. Environ. Dev. Sustain. 17, 1381-1412. Chapple K., 2015. Planning sustainable cities and regions. Towards equitable development. pp.307. Routledge, Oxon, UK. Childers D.L., Cadenasso M.L., Grove J.M., Marshall V., McGrath B., Pickett S.T.A., 2015. An ecology for cities: A transformational nexus of design and ecology to advance climate change resilience and urban sustainability. Sustainability 7, 3774-3791. DOI: 10.3390/su7043774. Colombo R., 2016. Unpreceded rise in cities disclosing climate strategies. pp.3. Raffaella.colombo@cdp.net. Dasgupta S., Lapla B., Murray S., Wheeler D., 2009. Sea-level rise and storm surges: A comparative analysis of impacts in developing countries. World Bank Policy Research Working Paper (42) WPS4901. World Bank, Washington DC. De Las Heras A., 2014. Sustainability science and technology. An introduction, 322pp. CRC Press, Taylor and Francis Group, Boca Roca, Fl. Diaz P., Stanek P., Frantzeskaki N., Yeh D., 2016. Shifting paradigms, changing waters: Transitioning to integrated urban water management in the coastal city of Dunedin, USA. Sustainable Cities and Society 26, 555-567. Do Thi Thu Huong, Tran Dinh Lan, 2014. Da Nang Ports. In: Environmental management of seaports in Vietnam. Tran Dinh Lan, Luc Hens, Cao Thi Thu Trang, Do Thi Thu Huong Eds., pp.316. Publishing House for Science and Technology, Hanoi, Vietnam. Duhem B., 2005. Introduction. In: Green structure and urban planning. Final report, pp.13-14.A.C. Werquin, B. Duhem, G. Lindholm, B. Oppermann, S. Pauleit, S. Tjallingii Eds. Office for Official publications of the European Communities. Luxemburg. Duong Thanh Nhi, Chu The Cuong, Tran Dinh Lan, 2014. The ports of Hai Phong. In: Environmental management of seaports in Vietnam. Tran Dinh Lan, Luc Hens, Cao Thi Thu Trang, Do Thi Thu Huong Eds., 177-219. Publishing House for Science and Technology, Hanoi, Vietnam. Giffinger R., Fertner C., Kramar H., Kalasek R., 2007. Smart cities: ranking of European medium-sized cities. Vienna University of Technology, Vienna, Austria. Godschalk D.R., 2007. Land use planning challenges: Coping with conflicts in visions of sustainable development and livable communities. Journal of the American Planning Association 70(1), 5-13, DOI: 10.1080/01944360409876334. Griggs D., Stafford-Smith M., Gaffney O., Rockström J., Öhman M.C., Shyamsundar P., Steffen W., Glaser G., Kanie N., Noble I., 2013. Policy: Sustainable development goals for people and planet. Nature 495, 305-307. Haase, D., 2015. Reflections about blue ecosystem services in cities. Sustainability of Water Quality and Ecology 5, 77-83. Hallegate S., Green C., Nicholls R.J., Corfee-Morlot J., 2013. Future flood losses in major coastal cities. Nature Climate Change 3, 802-806. Hassan A.M., Lee H., 2015. The paradox of the sustainable city: Definition and examples. Environ. Dev. Sustain. 17, 1267-1285. Henn R., Hoffman A.J., 2013. Constructing green. The social structures of sustainability. pp.398. MIT Press, Cambridge, Ma. Hinrichsen D., 1998. Coastal waters of the world. Trends, threats, and strategies. pp.275. Island Press, Washington DC. Hoekstra A. Y., Chapagain A. K., 2007. Water footprints of nations: Water use by people as function of their consumption pattern. Water Resources Management 21, 35-48. Huang G.L., Zhou W.Q., Cadenasso M.L., 2011. Is everyone hot in the city? Spatial pattern of land surface temperatures, land cover and neighborhood socioeconomic characteristics in Baltimore M.D. J. Environ. Manag, 92, 1753-1759. IDF-International Diabetes Federation, 2015. IDF atlas, 7th ed. Brussels, Belgium. IPCC-Intergovernmental Panel on Climate Changes, 2007. Climate change 2007 - Impacts, adaptation, and vulnerability. Contribution of working group III to the fourth assessment report of the IPCC. Cambridge University Press, NY. IPCC-Intergovernmental Panel on Climate Changes, 2014. Climate change 2014. Synthesis Report-Longer report, pp.116. United Nations, New York. James P., 2015. Urban sustainability in theory and practice. Circles of sustainability, pp.260. Earthscan from Routledge, Oxon, UK. Jung H.S., Jeong C.S., Lee Y.W., et al., 2009. An intelligent ubiquitous middleware for U-city: Smart UM. Journal of Information Science and Engineering 25, 375-388. Kabisch N., Strohbach M., Haase D., Kronenberg J., 2016. Urban green space availability in European cities. Ecological Indicators 70, 586-596. Kennedy S., Sgouridis S., 2011. Rigorous classification and carbon accounting principles for low and Zero Carbon Cities. Energy Policy 39, 5259-5268. Khazaei, M., Razavian, M.T., 2013. Sustainable Urban Development (an innovative approach in the development of cities around the world). International Research Journal of Applied and Basic Sciences 4, 1543-1547. Le Xuan Quynh, 2014. Environmental management system in ports. In: Environmental management of seaports in Vietnam. Tran Dinh Lan, Luc Hens, Cao Thi Thu Trang, Do Thi Thu Huong Eds, pp.115-148. Publishing House for Science and Technology, Hanoi, Vietnam. Luccarelli M., Roe P.G. (Eds.), 2012. Green Oslo. Visions, planning and discourse. Ashgate, Farnham, UK. Malcolm L., 2004. Integrated design for sustainable buildings. ASHRAE Journal 46, S22-S26, S28-S30. For the summer performance assessment of extensive green roofs in a Mediterranean coastal climate. Energy and Buildings 63, 1-14. Mnowlton K., Lynn R., Goldberg R.A., Hogrefe C., Rosenthal J., Kinney P.L., 2007. Projecting health-related mortality impacts under a changing climate in the New York City region. Am. J. Public Health 07, 2028-2034. MONRE-Ministry of Natural resources and Environment, 2012. Climate change and sea level rise scenarios for Vietnam. Hanoi, Vietnam. MONRE-Ministry of Natural Resources and Environment, 2015. State Report of Environment 2011-2015, Hanoi, Vietnam. Mueller N., Rojas-Rueda D., Basagana X., Cirach M., Cole-Hunter T., Dadvand P.,Donaire-Gonzalez D., Foraster M., Gascin M., Martinez D., Tonne C., Triguero-Mas M., Valentin A., Niewenhijsen M., 2016. Urban and transport planning related exposures and mortality: A health impact assessment for cities. Environmental Health Perspectives. DOI: 10.1289/EHP220. Also available at http://ehp.niehs.nih.gov/eph220/. Neirott P., De Marco A., Cagliano A.C., Mangano G., Scorrano F., 2014. Current trends in smart city initiatives: Some stylised facts. Cities 38, 25-36. Nguyen Van Thang, Nguyen Trong Hieu, Tran Thuc, Pham Thi Thanh Huong, Nguyen Thi Lan, Vu Van Thang, 2011. Climate change and its impacts in Vietnam. Science and Technology Publishing House, Hanoi, Vietnam, 259pp (in Vietnamese). Nguyen Van Thanh, 2014. Applying GCIF & ISO37120 for Building Hai Phong Green Port City. Report at the London Conference, 17-18 Nov. 2014. Olivien F., Di Pema C., D’Orazio M., Olivien N., Neila J., 2013. Experimental measurements and numerical model for the summer performance assessment of extensive green roofs in a Mediterranean coastal climate. Energy and Buildings, 63, 1-14. Olsen S.B., 2003. Frameworks and indicators for assessing progress in integrated coastal management initiatives. Ocean & Coastal Management 46, 347-361. Schnitzer H. Resource efficient and clean urban technologies, 2015. In Gianetti B.F., Almeida C.M.V.B., Agostinho F., Bonilla S.H. Eds. Advances in Cleaner Production. Proceedings of the 5th International Workshop, UNIP, Sao Paulo, SP, Brazil. May 20th-22nd, 2015, p.20. Taghvaei, M., 2013. Urban sustainable development and the factors affecting it (Case Study: Kermanshah). Urban Sociological Studies 3, 1-22. Tran Dinh Lan, Luc Hens, Cao Thi Thu Trang, Do Thi Thu Huong, 2014. Environmental management of seaports in Vietnam, pp.316. Publishing House for Science and Technology, Hanoi, Vietnam. Ülpre H., Eames I., 2014. Environmental policy constrains for acidic exhaust gas scrubber discharges from ships. Marine Pollution Bulletin 88, 292-301. DOI: 10.1016/j.marpobul.2014.08.027. UNDP-United Nations Development Programme, 2007. Fighting climate change: Human solidarity in a divided world. Human Development Report 2007/2008. United Nations, NY. UN-United Nations, 1992. Agenda 21: The United Nations Programme of Action from Rio. United Nations, New York. Available on line at http//www.un.org/esa/dsd/agenda21/res_agenda21_00.shtm (last accessed November 11th, 2016). UN-Habitat, 2009. Planning sustainable cities. Global report on human settlements 2009, pp.306. Earthscan, Sterling, Va. Upton S., 2015. Organisation for Economic Cooperation and Development. The OECD Observer, suppl. OECD Yearbook 2015 (Jun 2015), 64-65. Vadineanu A., 2001. Sustainable development: Theory and practice regarding the transition of socio-economic systems towards sustainability, pp.304. Tip Art Group Publishing and Printing Company, Bucharest, Romania. Vardoulakisq E., Koromanis B., Fotiadi A., Mihalakakov G., 2013. The urban heat island effect in a small Mediterranean city of high summer temperatures and cooling energy demands. Solar Energy 94, 128-144. Varol, C., Ercoskun, O., Gurer, Y., 2010. Local participatory mechanisms and collective actions for sustainable urban development in Turkey. Habitat International 35, 9-16. Vu Thanh Ca, Du Van Toan, Nguyen Van Tien, Nguyen Hoang Anh, Nguyen Hai Anh, Tran The Anh, Vu Thi Hien, 2010. Some preliminary results and numerical model for inundation calculation of Haiphong coastal area in the climate change and sea level rise. Journal of Marine Science and Technology, 10(2), 45-62. Vu Van Hieu, Le Xuan Quynh, Pham Ngoc Ho, Hens L., 2013. Application of GIS and modeling in health risk assessment for urban road and mobility. Environ. Sci. Pollut. Res. 20, 5138-5149, DOI: 10.1007/s11356-013-1492-5. WB-World Bank, 2010. Natural hazards, unnatural disasters: The economics of effective protection. International Bank for Reconstruction and Development. World Bank Publications, Washington DC. WHO-World Health Organization, Regional Office for Europe, 2016. Towards environmentally sustainable health systems in Europe. A review of the evidence. Publications of the WHO Regional Office for Europe, Copenhagen, Denmark. Zlender V., Thompson C. W., 2016. Accessibility and use of peri-urban green space for inner-city dwellers: A comparative study. Landscape and Urban Planning, in press.